Electron Spin Resonance (ESR) in detection of aquatic pollution through host-parasite relationship - Lucas Aparecido Rosa Leite; Angela Kinoshita; Oswaldo Baffa; Rodney Kozlowiski de Azevedo; Vanessa Doro Abdallah (Revista Ambiente & Água, 2018)
Aquatic environmental pollution due to negative human activities remains a major problem. Bioindicators that primarily describe the total concentration of the respective pollutant are very useful tools to aid in the chemical analysis of water in order to obtain knowledge about the levels of pollutants in the environment. This study therefore used Electron Spin Resonance Spectroscopy (ESR) to detect the presence of transition metals (copper, iron and manganese) and possible radicals present in samples of Neoechinorhynchus curemai and its host tissues Prochilodus lineatus, as well in water and sediment of the Batalha River, at the same sample site where fish were collected. Spectral analysis of samples showed the presence of three metals (Cu2+, Fe3+ and Mn2+), in addition to nitric oxide (NO) and humic acid (HA). Quantification of the elements in the samples was possible only for Cu detected in the spectrum of parasites, which was equivalent to 2 ppm. ESR proved to be efficient in the detection of transition-metal ions (Cu2+, Fe3+ and Mn2+), in addition to NO and HA. However, the low concentration values of these compounds in P. lineatus tissues (liver, muscle and intestine) and in the water and sediment samples collected did not allow their quantification, as they were below the limit of detection. It can be concluded that N. curemai had the capacity to accumulate these ions, especially copper.